2020
DOI: 10.3390/ani10101860
|View full text |Cite
|
Sign up to set email alerts
|

Beet Pulp: An Alternative to Improve the Gut Health of Growing Pigs

Abstract: The present study aimed to investigate the effects of dietary fiber on the gut health of growing pigs. In total, 30 growing pigs with an initial average body weight of 45.8 ± 2.78 kg were divided into three groups with 10 replicates per treatment, and one pig per replicate. The treatments included a corn–soybean meal-based diet (control group, 1.5% crude fiber (CF)), corn–soybean meal + beet pulp-based diet (beet pulp group, 5.74% CF) and corn–soybean meal-based diet (feed intake-pairing group (pairing group);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
(55 reference statements)
1
10
0
Order By: Relevance
“…In addition, SCFAs are the most critical and pleiotropic functional components of microbe-to-host signaling (56). It is now well-established that SCFAs modulate colonic motility by stimulating serotonin secretion from gut enterochromaffin cells (56,57) and SCFAs are closely related to intestinal growth and barrier function (58). In the present study, we observed a significant decrease in the concentration of propionic acid in both heroin dependent mice and FMT mice (Figure 6A) compared to controls.…”
Section: Discussionsupporting
confidence: 60%
“…In addition, SCFAs are the most critical and pleiotropic functional components of microbe-to-host signaling (56). It is now well-established that SCFAs modulate colonic motility by stimulating serotonin secretion from gut enterochromaffin cells (56,57) and SCFAs are closely related to intestinal growth and barrier function (58). In the present study, we observed a significant decrease in the concentration of propionic acid in both heroin dependent mice and FMT mice (Figure 6A) compared to controls.…”
Section: Discussionsupporting
confidence: 60%
“…Studies on ADG and FCR changes after SBP inclusion in pig diets have obtained inconsistent results. It was reported that the inclusion of SBP in pigs’ diet led to lower ADG [ 18 , 51 ]. However, Bruininx et al [ 52 ] reported that including 10% of SBP into the diet increased the FCR during the growing period.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that SBP contains similar gross energy and crude protein contents compared to corn grains [ 17 ]. Additionally, SBP contains fibre that is fermentable, has a high water-binding capacity and can alter the physical and chemical properties of the digestive tract, thus affecting feed intake and animal growth [ 18 , 19 , 20 ]. The fermentation of dietary fibre, such as SBP, in the gut promotes the multiplication of bacterial populations such as those of Lactobacillus and Bifidobacterium , which are generally considered to be beneficial to intestinal health, in part by preventing colonisation by opportunistic pathogens [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Supplementing SBP with a cocktail of carbohydrases such as xylanase, cellulase, and β-glucanase, improved the utilization of energy, protein, dry matter, and fiber as well as increasing the production of VFA in growing pigs [ 27 ]. Improvements in gut microbiota and gut health was also observed in growing pigs fed SBP [ 174 ]. A study by Gebbink et al [ 175 ] introduced SBP to weanling pigs and there was some evidence that SBP supported the increased production of VFA and reduced the population of harmful bacteria in the gut; however, it did not affect growth performance of piglets.…”
Section: Fiber-rich Feed Ingredientsmentioning
confidence: 99%